Fixed Point Theorems for Hybrid Mappings - Maria Samreen; Tayyab Kamran; Erdal Karapinar (The Scientific World Journal)
We obtain some fixed point theorems for two pairs of hybrid mappings using hybrid tangential property and quadratic type contractive condition. Our results generalize some results by Babu and Alemayehu and those contained therein. In the sequel, we introduce a new notion to generalize occasionally weak compatibility. Moreover, two concrete examples are established to illuminate the generality of our results.